2014
DOI: 10.5194/acp-14-1853-2014
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation by fertile soil dusts: relative importance of mineral and biogenic components

Abstract: Abstract. Agricultural dust emissions have been estimated to contribute around 20 % to the global dust burden. In contrast to dusts from arid source regions, the ice-nucleating abilities of which have been relatively well studied, soil dusts from fertile sources often contain a substantial fraction of organic matter. Using an experimental methodology which is sensitive to a wide range of ice nucleation efficiencies, we have characterised the immersion mode ice-nucleating activities of dusts (d < 11 µm) extract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
259
6
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 218 publications
(293 citation statements)
references
References 93 publications
25
259
6
3
Order By: Relevance
“…4a, b; some of the elements found in smaller amounts: O, F, Na, Cl and K). It has long been known that SOM serves as a reservoir of nutrients, such as N, P and S (Paul, 2007). As for the samples analyzed here, all the particles categorized as organ- (e) Soot-like particle.…”
Section: Identification Of Particle Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…4a, b; some of the elements found in smaller amounts: O, F, Na, Cl and K). It has long been known that SOM serves as a reservoir of nutrients, such as N, P and S (Paul, 2007). As for the samples analyzed here, all the particles categorized as organ- (e) Soot-like particle.…”
Section: Identification Of Particle Typesmentioning
confidence: 99%
“…This may suggest that there was no measurable contribution of microorganisms (e.g., bacteria and fungal spores) to the numbers of the agricultural soil dusts or IN examined here, although the possibility of the presence of some P-free microorganisms or plants (or their fragments) cannot be ruled out. Organic matter in soils is composed of a variety of macromolecules, such as lignin, cellulose, hemicellulose, protein, lipids, humic-like substances (e.g., humic acid and fulvic acid) and so on (Paul, 2007). So far, freezing experiments with certain standard humic-like substances have indicated that while they can act as IN under mixed-phase cloud conditions (Fornea et al, 2009;Wang and Knopf, 2011;Knopf and Alpert, 2013;Rigg et al, 2013;O'Sullivan et al, 2014), they are much less effective as IN than fertile soil dusts (O 'Sullivan et al, 2014).…”
Section: Identification Of Particle Typesmentioning
confidence: 99%
“…However, estimates regarding the contribution of agricultural areas to the global dust burden are not very well confined and range from less than 10% [Tegen et al, 2004] to 20-50% [Funk and Reuter, 2006;Forster et al, 2007;Ginoux et al, 2012]. Nevertheless, due to the high mass fraction of presumably ice-active biological material accompanying agricultural soil dusts, even a minor contribution of soil dust sources to the total atmospheric dust burden may have a significant impact on the abundance of atmospheric particles nucleating ice in mixed-phase clouds [Conen et al, 2011;O'Sullivan et al, 2014]. In addition, atmospherically transported agricultural soil dust particles carry not only primary biological particles but also organic matter (OM) in various forms, such as free organic matter (e.g., leaf debris), organo-mineral complexes, and secondary organic compounds [Ellerbrock et al, 2005;Kögel-Knabner et al, 2008;Conen et al, 2011;O'Sullivan et al, 2014;Conen et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory studies have confirmed that soil dusts may include much more efficient INPs than desert dusts and clay minerals [Isono and Ikebe, 1960;Fornea et al, 2009;Conen et al, 2011;O'Sullivan et al, 2014;Tobo et al, 2014]. Therefore, soil dusts may initiate the formation of ice in droplet and mixed-phase clouds.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of surface coatings and aging have also been investigated for BC and dust, often showing that surface treatment generally decreases and can suppress the nucleating ability of the studied particles under atmospheric conditions [Cziczo et al, 2009;Möhler et al, 2005]. The nucleating efficiency of various other atmospheric aerosols such as bacteria [Levin and Yankofsky, 1983], organic acids [Zobrist et al, 2006], biomass burning particles [Petters et al, 2009], soil dust [O'Sullivan et al, 2014], and more recently, sea salts [Wise et al, 2012] have also been extensively studied. Most of the laboratory studies mentioned here have been connected to theory and have therefore strongly contributed to the emergence of a reliable heterogeneous ice nucleation modeling framework based on CNT.…”
Section: Introductionmentioning
confidence: 99%